2006
DOI: 10.1002/hpm.858
|View full text |Cite
|
Sign up to set email alerts
|

Assessing uncertainty in outsourcing clinical services at tertiary health centers

Abstract: When tertiary health centers face capacity constraint, one feasible strategy to meet service demand is outsourcing clinical services to qualified community providers. Clinical outsourcing enables tertiary health centers to meet the expectations of service timeliness and provides good opportunities to collaborate with other health care providers. However, outsourcing may result in dependence and loss of control for the tertiary health centers. Other parties involved in clinical outsourcing such as local partner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…The third implication of the study is about the various reasons for the outsourcing of different clinical, as well as non-clinical services and most of the international literature tends to emphasize the financial and strategical advantages as the reasons behind outsourcing (Billi et al , 2007; Raeissi et al , 2018). In line with the existing literature, our findings also show that the concentration on core services, capital expenditure reduction, better management control, better access to expertize and work flexibility are the driving forces for outsourcing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The third implication of the study is about the various reasons for the outsourcing of different clinical, as well as non-clinical services and most of the international literature tends to emphasize the financial and strategical advantages as the reasons behind outsourcing (Billi et al , 2007; Raeissi et al , 2018). In line with the existing literature, our findings also show that the concentration on core services, capital expenditure reduction, better management control, better access to expertize and work flexibility are the driving forces for outsourcing.…”
Section: Discussionmentioning
confidence: 99%
“…Outsourcing allows a tertiary health center to become more specialized in concerned services (Aziz et al , 2017; Billi et al , 2007). Studies from different countries such as USA, Taiwan and some of the Eastern Mediterranean regions found that outsourcing allows a tertiary health center to concentrate on the management of core mission and advance its distinct specialty to achieve its strategic goals (Guimaraes and Carvalho, 2011; Billi et al , 2007).…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations